Electrical Stimulation for Pelvic Floor Disorders - Martellucci, Jacopo (Springer International Publishing : Imprint: Springer, 2015)
This book will enable the reader to gain a sound understanding of contemporary and futuristic evidence-based interventions and assessment procedures for pelvic floor disorders. It gathers the experiences of some of the most important experts on electrical stimulation techniques, offering a multidisciplinary and problem-oriented approach organized according to therapeutic goals. Interventions are recommended that are consistent with theory and display clinical efficacy for specific disorders, including urinary incontinence or retention, fecal incontinence, constipation, pelvic pain, sexual dysfunction, and neurological diseases involving the pelvic floor. All of the surgical or rehabilitative techniques requiring electrical stimulation for the treatment of these disorders are explored, and essential background information is provided on functional anatomy, neurophysiology, and concepts in electrotherapy. This volume will be a very useful tool for urologists, general or colorectal surgeons, gynecologists, and anesthesiologists, and also physiotherapists and alternative medicine practitioners (a specific chapter focuses on electroacupuncture). It will assist in their clinical practice as they seek to help the very many patients who suffer from any of the wide range of functional pelvic floor disorders.